Minimally Invasive Medial Plating of Low-Energy Lisfranc Injuries: Preliminary Experience with Five Cases - Jorge Javier del Vecchio; Mauricio Ghioldi; Nicolás Raimondi; Manuel De Elias (Advances in Orthopedics)
Fracture dislocations involving the Lisfranc joint are rare; they represent only 0.2% of all the fractures. There is no consensus about the surgical management of these lesions in the medical literature. However, both anatomical reduction and tarsometatarsal stabilization are essential for a good outcome. In this clinical study, five consecutive patients with a diagnosis of Lisfranc low-energy lesion were treated with a novel surgical technique characterized by minimal osteosynthesis performed through a minimally invasive approach. According to the radiological criteria established, the joint reduction was anatomical in four patients, almost anatomical in one patient (#4), and nonanatomical in none of the patients. At the final follow-up, the AOFAS score for the midfoot was 96 points (range, 95–100). The mean score according to the VAS (Visual Analog Scale) at the end of the follow-up period was 1.4 points over 10 (range, 0–3). The surgical technique described in this clinical study is characterized by the use of implants with the utilization of a novel approach to reduce joint and soft tissue damage. We performed a closed reduction and minimally invasive stabilization with a bridge plate and a screw after achieving a closed anatomical reduction.